Ethical Conflicts in Secular Education: Narrative Inquiry of French Educators in Faith-Diverse Classrooms - Camille Rousseau; Théo Girard; Sophie Vidal (Yayasan Adra Karima Hubbi, 2024)
Background. In secular education systems such as France’s, teachers are often positioned at the intersection of institutional neutrality and the growing religious diversity of their students. This tension can generate ethical conflicts as educators navigate complex classroom dynamics involving faith expression, laïcité (secularism), and cultural sensitivity. Purpose. This study explores how French educators experience and respond to ethical dilemmas in faith-diverse classroom settings within the framework of a secular public education system.Method. Using a narrative inquiry approach, data were collected from in-depth interviews with 18 secondary school teachers across urban and suburban regions of France. Thematic analysis revealed recurring tensions related to student religious expression, curricular constraints, parental expectations, and institutional ambiguity regarding secular norms. Teachers reported using various coping strategies, including silent negotiation, personal compromise, and reliance on informal peer networks. Results. The findings highlight a dissonance between policy and practice, and underscore the need for clearer ethical guidelines, teacher training, and institutional support in navigating pluralistic values. The findings contribute to scholarship on ethical pedagogy and secularism by foregrounding teacher agency and moral improvisation in pluralistic classrooms.Conclusion. This research contributes to the discourse on ethics in multicultural education by offering a grounded perspective on how secularism is lived, interpreted, and occasionally contested in everyday pedagogical practice.